Financial Foundations: Role of Family Financial Socialization and Literacy in Enhancing Financial Well-Being of Gen Z - Dhungana, Madan; Shrestha, Neharika (Journal of Emerging Management Studies, 2025)
Purpose – This study explores the family financial socialization among Nepali Gen Z and examines its influence on their financial well-being. Specifically, it investigates how various financial socialization factors relate to financial well-being while also exploring the mediating role of financial literacy in navigating the financial future of youths. Design/methodology/approach – This study adopted a quantitative research design with a cross-sectional approach. It surveyed a purposive sample of 294 Gen-Z students (aged 18-28) from five colleges affiliated with Tribhuvan University's Faculty of Management in Kathmandu Valley, Nepal. A structured survey gathered data on family financial socialization, financial literacy, and financial well-being. The study utilized descriptive statistics, correlation analysis, and mediation analysis to examine the relationships between variables and test the hypotheses. Findings – The findings indicate that financial socialization positively impacts financial well-being. Financial literacy, instruction on money management, expected financial independence, and openness to family finances positively affected financial well-being (p<0.001). Mediation analysis revealed that financial literacy partially mediated all relationships. Conclusion – Financial literacy is crucial in enhancing financial well-being through family financial socialization factors. The study highlights the importance of improving financial literacy and fostering supportive family financial behaviors to strengthen financial well-being. Implications: This paper has two implications. Theoretically, it provides a foundation for an in-depth study of financial socialization in the Nepalese context. Economy-wise, emerging adults need to pay attention to their financial well-being through various social agents shaping their financial environment and learning.